(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The presented scientific article highlights some effective methods for the effective use of sketching in the study of pencil drawing by future artist-teachers. It also shows the first stages of overcoming some problems, which appear in the process of learning pencil drawing.